Terapi Komplementer Dalam Keperawatan - Widyatuti Widyatuti (Fakultas Ilmu Keperawatan Universitas Indonesia, 2008)
AbstrakTerapi komplementer akhir-akhir ini menjadi isu di banyak negara. Masyarakat menggunakan terapi ini dengan alasan keyakinan, keuangan, reaksi obat kimia dan tingkat kesembuhan. Perawat mempunyai peluang terlibat dalam terapi ini, tetapi memerlukan dukungan hasil-hasil penelitian (evidence-based practice). Pada dasarnya terapi komplementer telah didukung berbagai teori, seperti teori Nightingale, Roger, Leininger, dan teori lainnya. Terapi komplementer dapat digunakan di berbagai level pencegahan. Perawat dapat berperan sesuai kebutuhan klien. AbstractComplementary therapy has emerged as a common health issue in the countries worldwide. People choose the complementary therapy based on many reasons such as belief, financial, avoiding the chemical reaction from medicine, and positive healing outcome. Nurse has great opportunity to deliver and develop complementary therapy supported by scientific evidences. Basically, the complementary therapy theoretical justification has been established by several nursing theory, as the Nightingale’s, Roger’s, Leininger’s and many others. Complementary therapy can be delivered in various prevention level. In accordance to the purpose, nurse should perform his/her role based on particular client’s needs.